Early Warning System to mitigate wheat blast in Bangladesh - CGIAR Platform for Big Data in Agriculture (2019)
The preliminary results suggest that the Decision Support System for Agro-technology Transfer (DSSAT)-NWheat model developed can satisfactorily simulate the growth and yield of wheat grown given coupled biotic stresses. The technology and methods applied can also potentially be applied to couple DSSAT models to other disease models